Attitude Stereotypes of English Language Adaptation in Linguocultural Space of Nordic Region - D. S. Borodina (Научный диалог, 2017)
The interaction of national languages in the Nordic region and the transnational English language as a tool of linguistic globalization are considered. The novelty of the research is seen in the fact that the interaction between English and national languages for the first time is interpreted in the context of stereotype attitude to the problem, on the one hand, by linguists and developers of language policy, on another hand, by other citizens. The relevance of the study due is determined by the fact that the model of attitude stereotypes is the key to understanding the national language policy in Denmark, Sweden and Norway and can be extrapolated to other regions. The author analyzes the debate among Scandinavian linguists regarding the displacement of the national languages from certain communicative spheres that formed the basis for the development of official documents regulating the status of the national and English languages. It is proved that most experts and ordinary citizens are supporters of the spread of English as a pragmatic tool of international communication, while a small minority of opponents call to protect the national language from its aggression. The author substantiates the thesis that a symbiosis of two attitude stereotypes developed in the Nordic region - the belief in the importance of preserving the status and functions of the national language and at the same time pragmatic acceptance of the expansion of English as a fact of modern language situation.